Implementation of the Political Party Financial Assistance Policy at the Central Executive Board of the Prosperous Justice Party (PKS) - Fitron Fajrurizkie; Udaya Madjid; Haikal Ali (Sean Institute, 2026)
Referring to the Audit Report (LHP) of the Audit Board of the Republic of Indonesia (BPK RI) for the 2022 Fiscal Year, it is stated that almost all political parties at the national, provincial, and regency/city levels in Indonesia exhibit the same issue, namely the inadequate implementation of financial assistance policies. This means that the management, accountability, and utilization of political party financial assistance have not been carried out in accordance with the prevailing laws and regulations. This study employed a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The informants in this study were the Director of Domestic Politics of the Ministry of Home Affairs, the Head of the Sub-Directorate for the Facilitation of Political Party Institutions, the Secretary General of the Prosperous Justice Party (PKS), the General Treasurer of the Central Executive Board (DPP) of PKS, the Financial Staff of the DPP PKS, and the BPK Audit Team. The results of this study indicate that: The implementation of the policy regarding the use of political party financial assistance, in terms of communication, resources (human resources and budget), bureaucratic structure, and disposition within the Central Executive Board of the Prosperous Justice Party, has not been effective and has not adequately supported the implementation of the use of political party financial assistance. Supporting factors include: (a) the availability of a legal framework regulating procedures for reporting accountability in the use of political party financial assistance; (b) the availability of sanctions; (c) the existence of a political party financial assistance audit team; (d) the availability of advanced technology; and (e) support from community elements incorporated in Non-Governmental Organizations (NGOs). Meanwhile, the inhibiting factors include: (a) the absence of clear percentage allocations for the use of political party financial assistance; (b) the absence of a special government institution specifically tasked with supervising, guiding, and socializing political parties; (c) the low quality and quantity of human resources; (d) the lengthy chain in the distribution of financial assistance; and (e) the financial assistance provided by the government to political parties is considered insufficient and inadequate.